(untitled) (Eurasian Research Bulletin, 2022)
In recent years, acute circulatory disorders in the brain have taken a high place in the world and in our country after cardiovascular diseases with mortality and disability rates. Stroke is the second most common cause of death in people worldwide. Every year, 450,000 people suffer from a stroke, and among European countries, Russia has the highest mortality rate from cerebrovascular diseases. According to the All-Russian Center for Preventive Medicine, 25% of men and 39% of women in our country die from cerebrovascular diseases. In our article, we discussed the importance of nutritional therapy in patients diagnosed with a stroke in the neurocritical care unit of the Bukhara branch of the Republican Scientific Center for Emergency Medicine. In total, 62 patients aged 45-69 years were selected for the experiment, of which 38 were men and 24 were women, changes in their general condition were observed within 14 days.